The Impact of Training Pattern According to the Function Exercises of Play to Develop the Some of Physical Capabilities and the Performance Accuracy of the Fundamental Skills in Soccer - Adnan Fadous Omar (Journal of Global Pharma Technology, 2018)
The research problem indicates a weakness and a decrease in the level of some special physical abilities as well as a decrease in the accuracy of the performance of some basic skills of the research sample and this is clearly evidenced by the slow movement and frequent maneuvers or cases and the failure of most cases scoring. The main objective of the research was to develop training pattern according to the training exercises in the training curriculum and to identify the effect of these training pattern on the research variables under consideration. The research hypotheses were statistically significant differences in the results of pre and posttests between the control and experimental research groups, statistical significance between the posttests between the control and experimental research groups and for the benefit of the experimental group. The researchers were used the experimental method, the sample of research consisted of (20) players representing the club (Ararat) the experimental group and (20) players representing the Club (Shaklawa) total control, the most important conclusions reached by researchers that the training models according to the exercise exercises used in The research has developed in some special physical abilities and accuracy of the performance of the basic skills used in the research. The recommendations are the adoption of training models according to the training exercises in the preparation stage and the two repetitive training methods in the training curricula of trainers.Keywords: Training pattern, Exercises, Physical capabilities, Fundamental skills and soccer.